2004
DOI: 10.1590/s0100-879x2004000300006
|View full text |Cite
|
Sign up to set email alerts
|

Urethroplasty using a bovine pericardium graft: an experimental study using normal urethras from dogs

Abstract: The use of bovine pericardium as a urethral patch to substitute a ventral segment of canine urethras was studied. Healing, epithelial growth, urethral permeability, fistulas, and calcification were analyzed. Thirty male mongrel dogs of medium and large size underwent resection of a ventral segment of the medial urethra measuring 2.0 x 0.5 cm, which was replaced with a bovine pericardium graft, treated with buffered glutaraldehyde and preserved in formaldehyde. Two running sutures of polygalactin 5-0 were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
8
2
Order By: Relevance
“…Although Lara et al [17] have reported a 20% success rate for a 6-month-long period, in our 3 weeks short-period study; all the histopathological findings were observed to be in favor of healing except in terms of urethrography, macroscopic observations and fibrosis. The near 100% success rate in our study may be due to the short period of the study and to the different type of animal used.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although Lara et al [17] have reported a 20% success rate for a 6-month-long period, in our 3 weeks short-period study; all the histopathological findings were observed to be in favor of healing except in terms of urethrography, macroscopic observations and fibrosis. The near 100% success rate in our study may be due to the short period of the study and to the different type of animal used.…”
Section: Discussioncontrasting
confidence: 78%
“…In the literature, urethral fistula repair with BP in the dog was carried out by Lara et al [17]. Although Lara et al [17] have reported a 20% success rate for a 6-month-long period, in our 3 weeks short-period study; all the histopathological findings were observed to be in favor of healing except in terms of urethrography, macroscopic observations and fibrosis.…”
Section: Discussionmentioning
confidence: 48%
“…Seven hundred fifteen patients underwent surgical reconstruction using pericardial grafts and had completed follow-up evaluations; 8 of these patients were published as case reports [8,10,11,31,37,40,47,48]. In addition, urologic reconstructive surgeries using pericardial grafts were performed on 139 animals comprising 45 rats [27,[54][55][56], 57 dogs [52,53,57,58], 31 rabbits [24,25,51], and 6 pigs [23]. The characteristics, overall outcomes, and the quality of all studies are summarized in Tables 1 and 2.…”
Section: Overall Studiesmentioning
confidence: 99%
“…Moreover, 1 of 5 (20%) dogs undergoing bladder reconstruction showed signs of urine leakage at the first week of the postoperative period, and there was a defect in the anastomosis part [57]. Moreover, treated BP grafts were used for the reconstruction of urethral defects in 30 dogs, during which 80% of the animals presented with urethrocutaneous fistulae without stenosis, and one dog with a successful procedure died of respiratory infections 4 months later [53].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation